2001
DOI: 10.1096/fj.01-0006com
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated diabetic glomerulopathy in galectin‐3/AGE receptor 3 knockout mice

Abstract: Several molecules were shown to bind advanced glycation end products (AGEs) in vitro, but it is not known whether they all serve as AGE receptors and which functional role they play in vivo. We investigated the role of galectin-3, a multifunctional lectin with (anti)adhesive and growth-regulating properties, as an AGE receptor and its contribution to the development of diabetic glomerular disease, using a knockout mouse model. Galectin-3 knockout mice obtained by gene ablation and the corresponding wild-type m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
137
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 37 publications
16
137
2
2
Order By: Relevance
“…Similar pathways have been implicated in the induction of cytokine adhesion molecules and growth factor synthesis by AGEs in various cell types (12,13,30). The pathways activated by the other receptors are less known, except for R3 which is involved in AGEs internalisation and clearance (31). Taken together, these results suggest that AGEs can activate human mesangial cells, mainly but not exclusively, through the binding to RAGE and its subsequent activation.…”
Section: Discussionsupporting
confidence: 61%
“…Similar pathways have been implicated in the induction of cytokine adhesion molecules and growth factor synthesis by AGEs in various cell types (12,13,30). The pathways activated by the other receptors are less known, except for R3 which is involved in AGEs internalisation and clearance (31). Taken together, these results suggest that AGEs can activate human mesangial cells, mainly but not exclusively, through the binding to RAGE and its subsequent activation.…”
Section: Discussionsupporting
confidence: 61%
“…Diabetic nephropathy is developed in RAGE-overexpressed mice (34). Also, it has been reported that diabetic glomerulopathy is accelerated in gelactin-3-deficient mice, suggesting that the interaction between AGEs and gelactin-3 blocks the negative effects of AGEs (6). In vitro studies suggest that AGEs activate signaling pathways similar to those induced by inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two binding proteins for AGEs were identified on the surface of endothelial cells, receptor for AGEs (RAGE) and lactoferrin-like polypeptide (homologous to lactoferrin) (4). The interaction between AGEs and their receptors plays a key role in the progression of diabetic atherosclerosis and glomerulopathy (5,6).…”
mentioning
confidence: 99%
“…For example, Park et al (24) have shown that intravenous administration of the soluble extracellular domain of RAGE, which was originally cloned from bovine pulmonary endothelial cells, efficiently suppressed diabetic atherosclerosis in apolipoprotein E-deficient mice. Second, Pugliese et al (25) have shown that diabetic glomerulopathy was rather accelerated in mice lacking galectin-3, a critical component of OST-48/80-K-H/galectin-3 complex (11) phages obtained from SR-A knock-out mice had the reduced capacity for endocytic degradation of AGE-BSA, which was 30% of that in wild-type cells. However, liver sinusoidal endothelial cells obtained from SR-A knock-out mice had capacity for endocytic degradation of AGE-BSA, which was indistinguishable from that of wild-type liver sinusoidal endothelial cells (27).…”
Section: Discussionmentioning
confidence: 99%